Assessment of the diagnostic reliability of brain CT and MRI in pediatric epilepsy patients - Mohamad Hasan Alam-Eldeen; Nahla Mohamed Ali Hasan (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Objective: Analysis of the role of CT and MRI in evaluation of pediatric epilepsy and their diagnostic utility to detect various pathologic entities at one center. Patients and methods: From April 2012 to April 2014, 181 children with epilepsy were underwent standardized CT and or MRI in the Department of Diagnostic Radiology at Sohag University Hospitals. We retrospectively analyzed whether lesions were detected and whether were precisely characterized by CT and or MRI. Results: Of the 181 patients included in the study, abnormalities were detected in 132 patients (73%) while normal brain images were found in 49 patients (27%). Of the 74 patients had CT only, abnormalities were detected in 73% while 27% were normal. Of the 89 patients underwent MRI only, abnormalities were detected in 74% while 26% were normal. Of the 18 patients underwent CT and MRI, abnormalities were detected in 67% while 33% were normal. Conclusion: Seizure disorders are among the most frequent neurologic problems that occur in childhood. MRI is the technique of choice and is superior to CT in identifying underlying cause. However, CT can serve as a screening modality and MRI would be performed to define abnormalities found on CT or in negative CT studies.